A Partial Molten Low‐Velocity Layer Atop the Mantle Transition Zone Beneath the Western Junggar: Implication for the Formation of Subduction‐Induced Sub‐Slab Mantle Plume. (9th February 2022) - Li, Guohui; Zhou, Yuanze; Ding, Lin; Gao, Yuan; Bai, Ling; Zhang, Heng; Hu, Le; Pan, Zhengyang; Ju, Changhui; Zhang, Dingding
Abstract: Deep subduction of plate generally could induce a partial molten low‐velocity layer (LVL) atop the mantle transition zone (MTZ) around the subduction zone. But the effects of the LVL to its upper lithosphere are less known, especially at the oceanward direction of subducted slab. Here, we image the seismic velocity structure atop the MTZ by matching the synthetics and the observed triplicated P ‐ and SH‐wave waveforms recorded by Xinjiang seismic network from four earthquakes in the southwestern Siberia. Our observations reveal a partial molten LVL atop the MTZ beneath the western Junggar (WJ) in the southwestern Central Asian Orogenic Belt. The SH‐wave velocity drop for the LVL is −5.6% which is larger than −4.4% of the P‐wave when its thickness is 29 km. It is inferred that the subducted Paleo‐Asian oceanic plate induces hydrous MTZ materials underneath the subducted slab to upwell to the upper mantle, and form the partial molten LVL. Combined with previous geophysical and geological results, we propose a new geodynamical process involving the lithosphere and MTZ underneath the subducted slab: the melt in the LVL is likely to upwell through slab window, which could be triggered by mid‐oceanic ridge subduction or self‐sustained buoyancy. This mode could account for the contemporaneous break‐off fossil oceanic plate, ocean island basalts‐type rocks, extensive A‐type granitoids, adakite, and porphyry Cu‐Au in the WJ during the late Carboniferous to early Permian. Plain Language Summary: Different types of rocks indicate a mantle plume or enriched asthenospheric mantle upwelling in the western Junggar (WJ) during the late Carboniferous to early Permian. However, the related magma origin is not clear. Through matching the synthetics and the observed triplicated P ‐ and SH‐wave waveforms, we detect a partial molten low‐velocity layer (LVL) atop the mantle transition zone (MTZ) beneath the WJ in northwestern Xinjiang, China. We infer that the formation of the LVL is related to the subduction of the Paleo‐Asian oceanic plate. The LVL may be the origin of a mantle plume flowing upward through slab window, which could help to explain the formation of break‐off fossil oceanic plate and various rocks, such as ocean island basalts‐type rocks, extensive A‐type granitoids, adakite, and porphyry Cu‐Au. Key Points: We explore P and SH velocities around depth of 410 km by triplicated waveform modeling A partial molten low‐velocity layer (LVL) is found atop the mantle transition zone in the western Junggar The LVL may be a mantle plume origin induced by the ancient subducted plate